Summary of temporal trends in pollutant levels observed in marine mammals - Borrel, Assumpción; J.H. Reijnders, Petter (J. Cetacean Res. Manage., 1999)
The present paper reviews reported time trends in concentrations and relative abundance of pollutants in marine mammals. Available information refers only to pinnipeds and cetaceans, mainly covers the period 1969-1988 and focuses on DDTs, PCBs and mercury. Although data are limited, there are indications that in the Canadian Arctic, mercury levels in marine mammals have increased in recent decades. By contrast, during the late 1970s and the 1980s, concentrations of DDTs and PCBs in marine mammals from highly polluted areas have tended to decrease. While this trend is likely lo continue for DDTs in the future, it is foreseen that until at least the first decades of the next century, PCB levels will stabilise as degradation is compensated by new inputs caused by the recycling of the fraction currently present in non-marine compartments.